2021
DOI: 10.18239/ocnos_2021.20.2.2407
|View full text |Cite
|
Sign up to set email alerts
|

relación entre comprensión lectora y vocabulario receptivo en estudiantes chilenos

Abstract: Si bien la bibliografía especializada ha descrito la existencia de un efecto posiblemente no causal entre vocabulario receptivo y comprensión lectora, y la posibilidad de un efecto acumulativo entre lectura de palabras y vocabulario, no se ha explorado si el efecto de vocabulario receptivo en comprensión lectora es invariante según los niveles de vocabulario receptivo, sexo y dependencia del colegio en la población chilena de quinto año básico. La muestra se conformó por 553 estudiantes balanceados en sexo y d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Similarly, in a study in which 2nd to 8th grade students were asked to answer multiple choice tests measuring different aspects of literal, inferential and critical levels, Gallego, Figueroa and Rodríguez (2019) found a general poor performance in all measures. In another study, Pezoa and Orellana (2021) reported that more than half of fifth-year students (10-11 years old) obtained low levels of comprehension when answering a standardized test (Dialect 2 ). In yet another study, Figueroa and Tobías (2018) asked students questions aimed at the literal, inferential and critical levels and found that fourth graders (9-10 years old) obtained low scores.…”
Section: General Performancementioning
confidence: 98%
“…Similarly, in a study in which 2nd to 8th grade students were asked to answer multiple choice tests measuring different aspects of literal, inferential and critical levels, Gallego, Figueroa and Rodríguez (2019) found a general poor performance in all measures. In another study, Pezoa and Orellana (2021) reported that more than half of fifth-year students (10-11 years old) obtained low levels of comprehension when answering a standardized test (Dialect 2 ). In yet another study, Figueroa and Tobías (2018) asked students questions aimed at the literal, inferential and critical levels and found that fourth graders (9-10 years old) obtained low scores.…”
Section: General Performancementioning
confidence: 98%